Somatic genetic alterations in a large cohort of pediatric thyroid nodules. Issue 6 (June 2019) - Pekova, Barbora; Dvorakova, Sarka; Sykorova, Vlasta; Vacinova, Gabriela; Vaclavikova, Eliska; Moravcova, Jitka; Katra, Rami; Vlcek, Petr; Sykorova, Pavla; Kodetova, Daniela; Vcelak, Josef; Bendlova, Bela
Abstract : There is a rise in the incidence of thyroid nodules in pediatric patients. Most of them are benign tissues, but part of them can cause papillary thyroid cancer (PTC). The aim of this study was to detect the mutations in commonly investigated genes as well as in novel PTC-causing genes in thyroid nodules and to correlate the found mutations with clinical and pathological data. The cohort of 113 pediatric samples consisted of 30 benign lesions and 83 PTCs. DNA from samples was used for next-generation sequencing to identify mutations in the following genes: HRAS, KRAS, NRAS, BRAF, IDH1, CHEK2, PPM1D, EIF1AX, EZH1 and for capillary sequencing in case of the TERT promoter. RNA was used for real-time PCR to detect RET/PTC1 and RET/PTC3 rearrangements. Total detection rate of mutations was 5/30 in benign tissues and 35/83 in PTCs. Mutations in RAS genes ( HRAS G13R, KRAS G12D, KRAS Q61R, NRAS Q61R) were detected in benign lesions and HRAS Q61R and NRAS Q61K mutations in PTCs. The RET/PTC rearrangement was identified in 18/83 of PTCs and was significantly associated with higher frequency of local and distant metastases. The BRAF V600E mutation was identified in 15/83 of PTCs and significantly correlated with higher age of patients and classical variant of PTC. Germline variants in the genes IDH1, CHEK2 and PPM1D were found. In conclusion, RET/PTC rearrangements and BRAF mutations were associated with different clinical and histopathological features of pediatric PTC. RAS mutations were detected with high frequency in patients with benign nodules; thus, our results suggest that these patients should be followed up intensively.